Clinical and subjective evaluation of implants in patients with hypodontia: a two‐year observation study. Issue 10 (8th August 2016) - Allen, P. Finbarr; Lee, Samuel; Brady, Paul
Abstract: Background: Hypodontia compromises appearance and function and is challenging to manage clinically. Objectives: To assess the impact of implant retained crowns on quality of life of patients and to determine clinical performance of implant retained crowns in these patients. Methods: In a 24‐month prospective observation study, patients with non‐syndromic mild hypodontia manifested with missing teeth in the anterior maxilla were included. Pre‐treatment screening included a clinical and radiographic examination and completion of an OHIP‐20. Narrow neck SLActive TiZr implants (Roxolid ®, Straumann AG, Switzerland) were provided and restored with single unit crowns. Implant stability was recorded at time of placement and abutment connection. Standardized radiographs were recorded at time of surgery, abutment connection and 12‐ and 24‐month follow‐up visits, and distance between implant shoulder and first bone contact was measured. Oral health‐related quality of life was calculated using OHIP‐20 scores at 12‐ and 24‐month visits compared with pre‐treatment scores. Pink (PES) and white (WES) aesthetic scores were used to objectively assess aesthetic outcome of treatment. Results: Twenty implants were placed in 12 patients (seven females, five males; mean [SD] age 19.33 [2.37] years). There was a significant improvement in oral health‐related quality of life following treatment ( P = 0.026), and the effect size of this change was 1.17 indicating a large clinically meaningful change. Mean PES and WES scores were high, indicated a satisfactory aesthetic outcome at 24 months. Crestal bone‐level changes were considered small. Conclusion: Favourable clinical outcomes were observed. Implant retained crowns had a large and clinically meaningful impact on quality of life of patients with hypodontia.